2012
DOI: 10.1007/s13197-012-0687-y
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of sorption isotherms of cassava (Manihot esculenta)

Abstract: Sorption isotherms of cassava were determined experimentally using a static gravimetric method at 30, 45 and 60°C and within the range of 0.10-0.90 water activity. At a constant water activity, equilibrium moisture content decreased with increasing temperature. The equilibrium moisture content increased with increasing water activity at a given temperature. The experimental results were modelled using seven sorption models using non-linear regression technique. Results demonstrated that the GAB model adequatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 74 publications
9
40
0
5
Order By: Relevance
“…The values of X m are in accordance to the values reported for fruits comprising 4-15 % on dry basis (Moreira et al 2008); however, Koua et al (2012) obtained values for cassava ranging from 6.16g H 2 O.100 g −1 to 3.66 g H 2 O.100 g −1 on dry basis. The (GAB) X m parameter is important because it can be related to the beginning of a series of chemical reactions of food decaying (Ferreira and Pena 2003).…”
Section: Resultssupporting
confidence: 89%
“…The values of X m are in accordance to the values reported for fruits comprising 4-15 % on dry basis (Moreira et al 2008); however, Koua et al (2012) obtained values for cassava ranging from 6.16g H 2 O.100 g −1 to 3.66 g H 2 O.100 g −1 on dry basis. The (GAB) X m parameter is important because it can be related to the beginning of a series of chemical reactions of food decaying (Ferreira and Pena 2003).…”
Section: Resultssupporting
confidence: 89%
“…It is comparable with the values for potato starch with an average value of 6.02% at a w ranges of 0.091-0.91 (Francisco et al, 2011). It is also comparable with the values for cassava flour which ranged from 2.1-11.2% at a w ranges of 0.1-0.9 (Blaise et al, 2014). The values are also comparable with those for castor bean flour which ranged from 4.77-18.91% at a w ranges of 0.37-0.87 (André et al, 2016).…”
Section: Model Evaluation Using Statistical Criteriasupporting
confidence: 85%
“…Moreover, Jain et al (2010) considered the Oswin as a superior model in describing the sorption characteristics of osmotically dehydrated papaya cubes. A number of studies have shown that GAB model has been successful in providing reasonable fit to sorption isotherms of several foods (Reddy and Chakraverty 2004;Erbas et al 2005;Togrul and Arslan 2006;Alam and Singh 2011;Rakshit et al 2011;Koua et al 2012). The results have shown that Smith model was in good agreement with the experimental sorption data of paddy throughout the whole water activity range.…”
Section: Modeling Sorption Isothermmentioning
confidence: 83%